Intra‐and Interpersonal Factors Buffer the Relationship Between Food Insecurity and Mental Well‐Being Among Middle Schoolers. (13th December 2020) - Brinkman, Jesse; Garnett, Bernice; Kolodinsky, Jane; Wang, Weiwei; Pope, Lizzy
ABSTRACT: BACKGROUND: Food insecurity (FI) is a significant predictor of feelings of isolation in children, as well as suicide ideation and depression. Using a census of public middle school‐aged children, we seek to determine whether FI is associated with suicide ideation and feelings of hopelessness and how individual and school community factors can alleviate or exacerbate this relationship. METHODS: We analyzed data from the 2015 Youth Risk Behavior Surveillance Survey, conducted statewide by the Vermont Department of Health and administered to all public middle schoolers (N = 13, 648). Questions were asked about FI, suicidal thoughts, feelings of hopelessness, perceptions of teaching and community care, physical activity, breakfast consumption, and demographics. Bivariate and cross‐tabular analyses were conducted in SPSS, and regressions and Sobel tests were conducted in STATA. RESULTS: Results show that FI is associated with decreases in psychological well‐being as measured by suicide ideation and feelings of hopelessness in students. However, students who reported eating breakfast regularly, feeling connected to their community or having a positive relationship with a teacher had significantly lower instances of suicide ideation and hopelessness. CONCLUSION: Suicide prevention programs should focus on enhancing community connection and student‐teacher relationships and increasing funding for breakfast programs in schools.